Teosofi, nasionalisme & elite modern Indonesia - Nugraha, Iskandar P.; Nugraha, Iskandar P. (Beji, Depok : Komunitas Bambu, 2011)
History of theosophical movements and nationalism in Indonesia.
Rev. ed. of: Mengikis batas Timur dan Barat.
Includes bibliographical references (p. 188-192) and index.
Keywords: Theosophy -- Indonesia; Nationalism -- Indonesia